2017
DOI: 10.1021/acsami.7b02804
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Magnetoresistance in Polymer Spin Valves

Abstract: In this work, both negative and positive magnetoresistance (MR) in solution-processed regioregular poly(3-hexylthiophene) (RR-P3HT) is observed in organic spin valves (OSVs) with vertical LaSrMnO (LSMO)/P3HT/AlO/Co configuration. The ferromagnetic (FM) LSMO electrode with near-atomic flatness is fabricated by a DC facing-target magnetron sputtering method. This research is focused on the origin of the MR inversion. Two types of devices are investigated in details: One with Co penetration shows a negative MR of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 45 publications
3
56
0
Order By: Relevance
“…[6,32] Moreover,the resistivity of the OSVs decreases with decreasing temperature.B ased on the previous investigations,t he temperature dependent resistivity and the negative MR in our OSVs can be attributed to the Co penetration into the active layer, which has also been proved by TEM and XPS measurement ( Supporting Information, Figures S12, S13). [27] Furthermore,c onsidering the root-mean-square (RMS) surface roughness of about 4.12 nm in our crystalline 100-nm Cu 3 (HHTP) 2 film (Supporting Information, Figure S4), the effective active barrier height is lower than 100 nm in the devices.T herefore,w ec an further infer that the spin dependent transport mechanism can be understood as amultistep-tunneling-dominated behavior.…”
Section: Zuschriftenmentioning
confidence: 93%
See 2 more Smart Citations
“…[6,32] Moreover,the resistivity of the OSVs decreases with decreasing temperature.B ased on the previous investigations,t he temperature dependent resistivity and the negative MR in our OSVs can be attributed to the Co penetration into the active layer, which has also been proved by TEM and XPS measurement ( Supporting Information, Figures S12, S13). [27] Furthermore,c onsidering the root-mean-square (RMS) surface roughness of about 4.12 nm in our crystalline 100-nm Cu 3 (HHTP) 2 film (Supporting Information, Figure S4), the effective active barrier height is lower than 100 nm in the devices.T herefore,w ec an further infer that the spin dependent transport mechanism can be understood as amultistep-tunneling-dominated behavior.…”
Section: Zuschriftenmentioning
confidence: 93%
“…Thethicknesses of the LSMO and Co electrodes were around 50 nm, while the thickness of Cu 3 (HHTP) 2 film was varied from 30 to 100 nm. To avoid the short circuit and minimize the effect of Co penetration, [27] the OSV device based on thicker Cu 3 (HHTP) 2 film (100 nm) was selected for systematical investigations (Figure 4b). Thei nterfacial structure between the Cu 3 (HHTP) 2 and Co layers were further investigated by the TEM-EDX and XPS (Supporting Information, Figures S12, S13).…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the long spin relaxation allows the study of triplet-to-singlet research since the first vertical OSV fabricated by Xiong et al, by which observed is negative MR at 11 K and found is apparent high field MR effect based on La 0.67 Sr 0.33 MnO 3 (LSMO) electrode. [43][44][45] In addition, some π-conjugated polymeric materials like poly(3-hexylthiophene) (P3HT), [28,46] poly(2,5-dioctyloxy-p-phenylenevinylene), [47] and P(NDI2OD-T2) [48] were also applied successfully in the OSV devices. [28] Actually, much more organic small molecules were applied in the OSV devices, including tris(8-hydroxyquinoline)aluminum (Alq 3 ), [21,[29][30][31][32][33] fullerene (C 60 and C 70 ), [34][35][36][37][38] rubrene, [39] pentacene, [40] bathocuproine, [41,42] and lanthanide molecules.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicated the presence of the Ni 2 + . [32,33] Figure 4c shows the high-resolution Mn 2p spectrum, where the two deconvoluted peaks at 641.3 and 653.4 eV were attributed to Mn 2 + , while the other two deconvoluted peaks at 643.2 and 654.7 eV were attributed to Mn 3 + . [20,34] The high-resolution Co 2p spectrum in Figure 4d shows the co-existence of Co 2 + and Co 3 + , which were accordingly derived from the two deconvoluted peaks at 781.7 and 796.4 eV, and another two deconvoluted peaks at 779.5 and 794.4 eV, respectively.…”
Section: Resultsmentioning
confidence: 99%